Bisnis Online Menurut Perspektif Agama Islam - Ripiani, lita (CV ODIS, 2024)
The rapid advancement of information technology has significantly transformed human life, particularly in the economic sector. Online business, leveraging the internet as its primary medium, has emerged as a modern alternative to conventional commerce, enabling broader market reach without geographical limitations. In Indonesia, the development of online business continues to show a positive trend, supported by the growing number of internet users. This study examines the legal and ethical aspects of online business from an Islamic perspective. Islam, as a comprehensive religion, provides clear guidelines on trade, emphasizing principles like justice, transparency, and mutual consent to ensure alignment with Islamic law. Using a qualitative descriptive approach, this research analyzes the definitions, theoretical foundations, and evolution of online business practices, alongside their compliance with Islamic principles. The findings suggest that online business is permissible in Islam if it adheres to conditions such as the absence of fraud, usury (riba), and uncertainty (gharar). Additionally, online business can contribute positively to the Muslim economy if it upholds ethical and spiritual values, providing a responsible and sustainable pathway for entrepreneurs in the digital era.